Endophytic Beauveria bassiana induces biosynthesis of flavonoids in oilseed rape following both seed inoculation and natural colonization - Muola, Anne (JOHN WILEY & SONS LTD, 2026)
Background
Cultivation of oilseed rape Brassica napus is pesticide-intensive, and alternative plant protection strategies are needed because both pesticide resistance and legislation narrow the range of effective chemical pesticides. The entomopathogenic fungus Beauveria bassiana is used as a biocontrol agent against various insect pests, but little is known about its endophytic potential and role in plant protection for oilseed rape. First, we studied whether B. bassiana can establish as an endophyte in oilseed rape, following seed inoculation. To evaluate the plant protection potential of endophytic B. bassiana on oilseed rape, we next examined its ability to induce plant metabolite biosynthesis. In another experiment, we tested the effect of seed inoculation on seedling survival in a semi-field experiment.
Results
Beauveria bassiana endophytically colonized oilseed rape following seed inoculation, and, in addition, natural colonization was also recorded. Maximum colonization rate was 40%, and generally increased with inoculation time. Seed inoculation did not affect the germination probability or growth of oilseed rape, but B. bassiana inoculated seeds germinated more slowly compared to controls. Endophytic colonization of B. bassiana induced biosynthesis of several flavonoids in oilseed rape leaves under controlled conditions. In the experiment conducted in semi-field conditions, inoculated seedlings had slightly higher mortality compared to control seedlings.
Conclusion
Beauveria bassiana showed endophytic potential on oilseed rape via both natural colonization and seed inoculation, and it induced the biosynthesis of flavonoids. However, its use as an endophyte for plant protection against pests or pathogens for oilseed rape remains unclear.